Oncological and pregnancy outcomes after high-dose density neoadjuvant chemotherapy and fertility-sparing surgery in cervical cancer - Robova, Helena; Halaska, Michael J; Pluta, Marek; Skapa, Petr; Matecha, Jan; Lisy, Jiri; Rob, Lukas (Gynecologic oncology, 2014)
OBJECTIVE: 28 women under 35years with early-stage cervical cancer and strong desire for fertility preservation that do not fulfil standard criteria for fertility-sparing surgery (tumour larger than 2cm or with deep of infiltration more than half of stroma) were included in prospective study. METHODS: Dose-dense neoadjuvant chemotherapy (NAC) was performed on all 28 patients in 10-day intervals: cisplatin plus ifosfamide in squamous cell cancer (15 women-53.6%) or cisplatin plus doxorubicin in adenocarcinoma (13 women-46.3%). Patients underwent laparoscopic lymphadenectomy and vaginal simple trachelectomy after NAC. Patients with positive lymph nodes or inadequate free surgical margins underwent radical hysterectomy. RESULTS: No residual disease was found in 6 women (21.4%), microscopic disease was observed in 11 women (39.3%) and macroscopic tumour in was observed in 11 women (39.3%). Ten women (35.7%) lost fertility. Four women (20%) after fertility-sparing surgery recurred, two died of the disease (10%). Fertility was spared in 20 (71.4%) women and 10 of them became pregnant (50%). Eight women delivered ten babies (6 term and four preterm deliveries). There were two miscarriages in second trimester (in one woman) and one in first trimester. One woman underwent four unsuccessful cycles of IVF, one failed to become pregnant and one recurred too early. Two women underwent chemoradiotherapy for recurrence and lost chance for pregnancy. CONCLUSIONS: Downstaging by NAC in IB1 and IB2 cervical cancer before fertility-sparing surgery is still an experimental procedure, but shows some promise. Long-term results in relation to oncological outcome for this concept are still needed.
Keywords: Neoplasm Staging; Premature Birth; dospělí; Doxorubicin; Neoplasm, Residual; Carcinoma, Squamous Cell; Pregnancy outcome; Trachelectomy; lymfadenektomie; předčasný porod; cisplatina; Female; Neoadjuvant Therapy; léčba šetřící orgány; Adult; Cisplatin; Term Birth; ženské pohlaví; mladý dospělý; neoadjuvantní terapie; cervix uteri; Adolescent; Abortion, Spontaneous; lidé; staging nádorů; Lymph Node Excision; těhotenství; Pregnancy Outcome; reziduální nádor; nádory děložního čípku; Antineoplastic Combined Chemotherapy Protocols; ženská infertilita; protokoly protinádorové kombinované chemoterapie; Fertility-sparing surgery; Neoadjuvant chemotherapy; prospektivní studie; ifosfamid; Adenocarcinoma; Fertility outcome; Infertility, Female; Prospective Studies; spinocelulární karcinom; adenokarcinom; Young Adult; doxorubicin; samovolný potrat; Organ Sparing Treatments; výsledek těhotenství; hysterektomie; Uterine Cervical Neoplasms; Cervical cancer; Ifosfamide; Pregnancy; zachování plodnosti; Cervix Uteri; porod v termínu; mladiství; Hysterectomy; Fertility Preservation; Humans